Influence of Modeling Decisions on Three-Dimensional Finite Element Analysis of Two Existing Highway Bridges Subjected to Lateral Spreading. Issue 1 (2016) - Ghofrani, Alborz; McGann, Christopher R.; Arduino, Pedro
Three-dimensional finite element models are developed for the approaches of two Chilean bridges. A kinematic loading regime representative of postevent deformations associated with liquefaction-induced lateral spreading is used to analyze the models. Three important aspects of the modeling of this load case are assessed for such structures. First, the bridge deck and associated expansion gap and their effect on the overall response of the bridge–foundation–soil system are considered. The lateral resistance supplied by the bridge deck can play an important role in the general response of the model, and consideration of the expansion gap could lead to distinct pre- and postclosure deformation mechanisms. Second, elastic and elastoplastic constitutive responses in the deep foundations are explored, and the nonlinear nature of the drilled shafts is shown to be of essential importance. Finally, the effects of the inherent three-dimensional characteristics of each bridge are addressed. These effects are shown to play a significant role in the overall response of each bridge, which highlights the need for analytical procedures that consider three-dimensional effects.